2006
DOI: 10.1088/0965-0393/14/2/004
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in post forging errors for aerofoil forging using finite element simulation and optimization

Abstract: This paper reports on recent work in the development of a finite element (FE) based forging optimization methodology. It utilizes the commercial FE package ABAQUS and the optimization code VisualDOC. Taking into account the effect of die and press elastic deflections and thermal distortion in cooling, a direct compensation approach and optimized weighting factor method are used to achieve the optimized die shape for improved dimensional accuracy of forged aerofoil blades. The significant predicted reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…After 20seconds, the cooling system decreases the temperature of the part [4]. The simulation innumerical simulation softwareshowed the deformation of the tube, in comparison to the actual deformation in the factory [2]. In the factory, the 3-Dimensional Measurement Equipment we used to measure the diameter of the tube.…”
Section: The Numerical Simulation Of Tube Welding Without Mandrelmentioning
confidence: 99%
“…After 20seconds, the cooling system decreases the temperature of the part [4]. The simulation innumerical simulation softwareshowed the deformation of the tube, in comparison to the actual deformation in the factory [2]. In the factory, the 3-Dimensional Measurement Equipment we used to measure the diameter of the tube.…”
Section: The Numerical Simulation Of Tube Welding Without Mandrelmentioning
confidence: 99%
“…By contractions with the metallurgical test results, it indicated that the established model can predict the thermal deformation microstructure evolution process of 45Cr4NiMoV steel. The Deform-3D software was used to predict the microstructure evolution during deformation for heavy supporting roller [2] .…”
Section: Introductionmentioning
confidence: 99%
“…The major contributors to dimensional and shape errors in forged aerofoil components are press and die elasticity during forging, material spring back and thermal distortion at the cooling stage [1]. Due to the complexity of the hot forging process, forging design practice is largely based on the trial and error approach [2].…”
Section: Introductionmentioning
confidence: 99%